Analysis of Chronic Disease Direct Cost at Public Primary Health Cares in Indonesia (Bangladesh Journal of Medical Science, 2021)
Objectives: This study aims to analyze the of drug costs for patients with chronic diseases in the capitation system in public primary health cares (Public PHCs).Materials and Methods: This research is a quantitative study with an observational cross-sectional approach at 16 Public PHCs. Data collection used the retrospective method. The total sample was 293 outpatients in 2016.Results: The results showed that 63% of patients are female. The most patients are aged between 56-65 years (37%). The average drug cost for patients receiving more than 3 types of drugs is IDR 7,726. The biggest drug cost is patients with DM type 2 with which the average cost is IDR 7.400. And the metformin treatment is 17 (6%) patients with the cost IDR 4,500,-. Chi-square analysis shows that the quantity of drug items, type of disease and prescriptions there are have significant effect on drug cost (p-value 0.05). Drug prescriptions are an important component in managing chronic diseases patients. Prescribing costs provide important information in the sustainability of the management of chronic disease programs.Conclusion: This study recommends that the prolanis policy in public PHCs is focused on the elderly age group patients and female group.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.762-767